Treatment, no treatment and early death in Danish stage I lung cancer patients. (May 2019) - Christensen, Niels Lyhne; Dalton, Susanne; Ravn, Jesper; Christensen, Jane; Jakobsen, Erik; Rasmussen, Torben Riis
Highlights: Two thirds of Danish stage I lung cancer patients are surgically treated. Differences in outcome according to curative treatment were due to age and performance status. Treatment registration in the Danish Lung Cancer Registry can be improved. Histology, high-risk alcohol and comorbidity were associated with not undergoing treatment. Abstract: Background: Stage I lung cancer is curable with surgery as the treatment of choice. Other effective and curative treatments exist. Nevertheless, some patients only receive palliative treatment and some receive no treatment at all. Materials and methods: Using the Danish Lung Cancer Registry (DLCR), we assessed treatment distribution for a population-based Danish cohort of stage I lung cancer patients diagnosed from 2011 to 2014. We assessed one-year mortality according to treatment. Furthermore, in a nested case-control study based on data from medical records, we assessed the reason for not undergoing treatment among patients in favourable performance status (PS) with no treatment registration in the DLCR. Results: We identified 2985 patients, 68% (n = 2021) were treated surgically and 17% (n = 508) were managed with curative oncological therapy. The unadjusted odds ratio (OR) for death within one year was 2.5 (95% CI, 1.8–3.3) for the oncologically managed vs. the surgically treated. After adjusting for age, lung function and PS, the OR was 1.2 (95% CI, 0.8–1.9). Among 129 patients with a PS of 0–1 and no treatment registration, we established the reason for not undergoing treatment in 122 (95%). The majority (70%) were misclassified and did either not have lung cancer, had more advanced disease or were curatively treated. The 36 (30%) patients that did not undergo treatment, had a lower prevalence of adenocarcinomas (17 vs. 51%, p = 0.003), more comorbidites (median Charlson comorbidity index score 2 vs. 1, p < 0.001) and high alcohol intake (19 vs. 7%, p = 0.04) as compared to surgically treated controls. The primary reasons for no treatment were; comorbidity, patient decision and disease progression. Conclusion: Difference in outcome between the two major treatment groups was confounded by age, lung function and PS. Comorbidity, high alcohol intake and histology were associated with not undergoing curative treatment in spite of a favourable PS.